Monkeypox presenting as an isolated genital rash: a case report (Dermatology Reports, 2025)
Monkeypox has recently garnered global attention, particularly in 2022, due to a worldwide outbreak. It is a viral infection that begins as a rash on the face and then spreads to other parts of the body. In recent times, cases presenting as genital lesions have been reported, particularly among men who have sex with men (MSM). We present a unique case of a 20-year-old male from Riyadh, Saudi Arabia, who developed an isolated genital rash after engaging in heterosexual contact. This case represents one of the rare local monkeypox infections in Saudi Arabia and emphasizes the significance of considering sexual transmission outside of MSM populations. The patient initially presented with fever and a localized vesicular rash in the pubic area, which evolved into erythematous plaques on other parts of the body. Laboratory confirmation of monkeypox was attained, and supportive treatment was provided. Therefore, physicians should consider monkeypox when diagnosing sexually transmitted diseases that present as genital lesions and reinforce the importance of health education on safe sexual practices to decrease viral spread.